2018
DOI: 10.1007/s00167-018-4979-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased symptoms of stiffness 1 year after total knee arthroplasty are associated with a worse functional outcome and lower rate of patient satisfaction

Abstract: Purpose Symptoms of stiffness after total knee arthroplasty (TKA) cause significant morbidity, but there is limited data to facilitate identification of those most at risk after surgery. Stratifying risk can aid earlier directed treatment options. Methods A retrospective cohort consisting of 2589 patients undergoing a primary TKA was identified from an established arthroplasty database. Patient demographics, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and short form (SF) 12 scores w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 31 publications
(42 reference statements)
0
29
0
1
Order By: Relevance
“…The participants in our study described discontentment because they were not fully informed regarding the somewhat limited range of motion that could be expected postoperatively. A recent study showed that an improvement of five degrees in the range of motion in the knee after surgery along with an improved walking distance could increase the satisfaction rate by 6-8 times [49]. Other studies also agree with the effect of stiffness on satisfaction [50,51].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The participants in our study described discontentment because they were not fully informed regarding the somewhat limited range of motion that could be expected postoperatively. A recent study showed that an improvement of five degrees in the range of motion in the knee after surgery along with an improved walking distance could increase the satisfaction rate by 6-8 times [49]. Other studies also agree with the effect of stiffness on satisfaction [50,51].…”
Section: Discussionmentioning
confidence: 69%
“…In the current study the patients' course of recovery was not investigated, only if there were complications or not. So it was not known whether these patients met the range of motion and walking distance improvements reported in the literature [49].…”
Section: Discussionmentioning
confidence: 92%
“…One potential advantage of the WOMAC score is the separation of the component scores, evaluating pain, function and stiffness The Journal of Knee Surgery separately, which is not possible with the OKS. The components of the preoperative WOMAC score that include pain, 7,8 function, 8,11 and stiffness 11,25 have all been shown to be independent predictors of satisfaction after TKA. Despite this the threshold values identified in the current study for the preoperative WOMAC scores were poor predictors of dissatisfaction, being at best only 63% specific and sensitive to identify such patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that an improvement of five degrees in the range of motion in the knee after surgery along with an improved walking distance could increase the satisfaction rate by 6-8 times [49]. Other studies also agree with the effect of stiffness on satisfaction [50,51]. In the current study the patients' course of recovery was not investigated, only if there were complications or not.…”
Section: Discussionmentioning
confidence: 50%